Subjetividades em dívida: formação e sociedade de controle - LEMOS, Flávia Cristina Silveira (Universidade de Lisboa, 2023)
The paper presents a conceptual discussion on the production of a debt of subjectivities, in response to the excesses of contemporary society, generating illnesses, hatreds, resentments, strenuous search training, excessive demand for labor, unfair competition for positions and vacancies, exhaustive public exposure among other current issues to consider. Think these events of today is relevant and can contribute to various areas of knowledge, in that it interrogates the history of the present, with Deleuze, Foucault, Arendt, Negri, Cocco, Arendt, Levy, Bauman and Castells, among other researchers important production of contemporary subjectivities. It is stated as plus continuing education casualization of labor and commodification of affective and social relations generated suffering and difficult complex issues to develop and deal in contemporary.